Collaboration Matters: Honey Bee Health as a Transdisciplinary Model for Understanding Real-World Complexity. (10th October 2018) - Suryanarayanan, Sainath; Kleinman, Daniel Lee; Gratton, Claudio; Toth, Amy; Guedot, Christelle; Groves, Russell; Piechowski, John; Moore, Brad; Hagedorn, Deborah; Kauth, Dayton; Swan, Heather; Celley, Mary
Abstract: We develop a transdisciplinary deliberative model that moves beyond traditional scientific collaborations to include nonscientists in designing complexity-oriented research. We use the case of declining honey bee health as an exemplar of complex real-world problems requiring cross-disciplinary intervention. Honey bees are important pollinators of the fruits and vegetables we eat. In recent years, these insects have been dying at alarming rates. To prompt the reorientation of research toward the complex reality in which bees face multiple challenges, we came together as a group, including beekeepers, farmers, and scientists. Over a 2-year period, we deliberated about how to study the problem of honey bee deaths and conducted field experiments with bee colonies. We show trust and authority to be crucial factors shaping such collaborative research, and we offer a model for structuring collaboration that brings scientists and nonscientists together with the key objects and places of their shared concerns across time.